Enhancing healthcare planning using population data generated from mobile phone networks in Futaba County after the Great East Japan earthquake - Asaka Higuchi; Hiroki Yoshimura; Hiroaki Saito; Toshiki Abe; Michio Murakami; Tianchen Zhao; Isamu Amir; Naomi Ito; Chika Yamamoto; Saori Nonaka; Toyoaki Sawano; Yuki Shimada; et al. (Scientific Reports)
Abstract After the Great East Japan Earthquake, planning appropriate healthcare resource allocation was crucial. However, accurately estimating medical care demand was challenging due to substantial population fluctuations caused by extensive evacuations, compounded by the inaccuracy of conventional Resident Resister data in this context. This study employs population data generated from mobile phone network from 2019 to 2020 to conduct a detailed temporal and spatial population estimation in Futaba County, originally a complete evacuation zone. To enhance the precision of population estimates, population data independently collected by each municipality were used as reference data in the estimation process. Further, the utility of the estimated population data for calculating emergency transport rates was assessed. Our findings revealed discrepancies between daytime and nighttime populations within Okuma and Futaba Town, where median day/night population ratio exceeded three across both weekdays and weekends. Additionally, sex–age-adjusted emergency transport rates calculated using the estimated population demonstrated closer alignment with the national average compared to those calculated based on census data. This study demonstrates the importance of considering dynamic population data, such as that generated from mobile phone networks, in enhancing healthcare planning and ensuring that resources are efficiently allocated to meet communities’ evolving needs during recovery periods.